2021
DOI: 10.3390/ijms22094731
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrapping and Pinning down the Root Meristem; the Auxin–PLT–ARR Network Unites Robustness and Sensitivity in Meristem Growth Control

Abstract: After germination, the meristem of the embryonic plant root becomes activated, expands in size and subsequently stabilizes to support post-embryonic root growth. The plant hormones auxin and cytokinin, together with master transcription factors of the PLETHORA (PLT) family have been shown to form a regulatory network that governs the patterning of this root meristem. Still, which functional constraints contributed to shaping the dynamics and architecture of this network, has largely remained unanswered. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This approach can in principle be applied for the analysis of every signal perception and transduction process as long as a minimal set of elements and quantitative data are available or experimentally accessible, as has been demonstrated e.g. in the in-depth analysis of the PLT-auxin network during root zonation development in Arabidopsis thaliana ( Salvi et al, 2020 ; Rutten and Ten Tusscher, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach can in principle be applied for the analysis of every signal perception and transduction process as long as a minimal set of elements and quantitative data are available or experimentally accessible, as has been demonstrated e.g. in the in-depth analysis of the PLT-auxin network during root zonation development in Arabidopsis thaliana ( Salvi et al, 2020 ; Rutten and Ten Tusscher, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…While computational modeling has been used frequently in biomedical research since the early 2000s, its application to the plant field has started more recently ( Hübner et al, 2011 ; Holzheu and Kummer, 2020 ). Here, the growth and development of the root tip has been of particular interest ( Bruex et al, 2012 ; Muraro et al, 2016 ; Di Mambro et al, 2017 ; Rutten and Ten Tusscher, 2019 ; Salvi et al, 2020 ; Rutten and Ten Tusscher, 2021 ). Further computational studies in plants include the modeling of auxin signaling ( Vernoux et al, 2011 ) and transport pattern ( Band et al, 2014 ), and parts of the BR signaling ( Sankar et al, 2011 ; van Esse et al, 2012, 2013a ,b; Allen and Ptashnyk, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Values of parameters involved in baseline auxin production ( p auxin , baseline ) and degradation ( d auxin ), additional cell type-dependent auxin production ( celltypefactor ), gene expression-mediated upregulation of auxin production ( yucca 4 factor ) and auxin transport rates and directions (intracellular and intra-apoplastic diffusion D cell , D wall , PIN-mediated export p PIN , ABC-mediated export eff basal , AUX1-mediated import p AUX / LAX , baseline import inf pas ) are taken as equal or close to values from previous well-established model studies, dating back as far as the seminal study by Grieneisen et al (2007) . For these parameter settings, models were shown to produce qualitatively realistic and robust auxin patterns ( van den Berg et al, 2016 , 2021; Grieneisen et al, 2007 ; Mähönen et al, 2014 ; Rutten and Ten Tusscher, 2021 ; Salvi et al, 2020 ) consistent with shoot cut experiments ( Grieneisen et al, 2007 ), capable of simulating tropic responses ( van den Berg et al, 2016 ; Mähönen et al, 2014 ) consistent with more recent insights on the importance of root localized auxin production ( van den Berg et al, 2021 ; Rutten and Ten Tusscher, 2021 ; Salvi et al, 2020 ), and consistent with experimentally observed changes in auxin and meristem dynamics in response to mutations ( van den Berg et al, 2021 ; Salvi et al, 2020 ) . Under these parameter settings, the basic priming dynamics shown in Fig.…”
Section: Methodsmentioning
confidence: 99%